A Study of Women’s Power in Patriarchy on Nawal El Saadawi’s Novel Women at Point Zero - Zhanuar Zahro, Ilham; Hadi, Samsul; Hari Wibawa, Saptanto (International Journal Labs, 2024)
The novel Women at Point Zero by Nawal El Saadawi depicts the struggle of women in a patriarchal society. This work focuses on the experience of Firdaus, a woman who faces various forms of oppression. This study aims to explore the concept of women's power in the context of patriarchy as depicted in the novel. This study aims to understand how women's power is represented through the character of Firdaus and to analyze the strategies she uses to fight oppression. The approach used in this study is descriptive qualitative. Data were collected through in-depth reading of the novel, followed by identifying and classifying data related to the theme of women's power. Data analysis was carried out using Miles and Huberman's theory which includes data reduction, data presentation, and drawing conclusions. This study found six categories of women's power concepts displayed through Firdaus: the struggle against oppression, body control, the search for identity, radical decision-making, financial and emotional freedom, and rejection and victimization. Firdaus shows that women's power can be achieved through firm decisions and resilience in the face of injustice. Saadawi's work not only depicts oppression, but also highlights women's strength and resilience in the face of restrictive social norms. This research enriches the understanding of the dynamics of women's power in a patriarchal context, and provides new perspectives on women's struggles for freedom and identity.